Verification of Gamma Knife extend system based fractionated treatment planning using EBT2 film. Issue 12 (25th November 2013) - Natanasabapathi, Gopishankar; Bisht, Raj Kishor
Abstract : Purpose: : This paper presents EBT2 film verification of fractionated treatment planning with the Gamma Knife (GK) extend system, a relocatable frame system for multiple‐fraction or serial multiple‐session radiosurgery. Methods: : A human head shaped phantom simulated the verification process for fractionated Gamma Knife treatment. Phantom preparation for Extend Frame based treatment planning involved creating a dental impression, fitting the phantom to the frame system, and acquiring a stereotactic computed tomography (CT) scan. A CT scan (Siemens, Emotion 6) of the phantom was obtained with following parameters: Tube voltage—110 kV, tube current—280 mA, pixel size—0.5 × 0.5 and 1 mm slice thickness. A treatment plan with two 8 mm collimator shots and three sectors blocking in each shot was made. Dose prescription of 4 Gy at 100% was delivered for the first fraction out of the two fractions planned. Gafchromic EBT2 film (ISP Wayne, NJ) was used as 2D verification dosimeter in this process. Films were cut and placed inside the film insert of the phantom for treatment dose delivery. Meanwhile a set of films from the same batch were exposed from 0 to 12 Gy doses for calibration purposes. An EPSON (Expression 10000 XL) scanner was used for scanning the exposed films in transparency mode. Scanned films were analyzed with inhouse written MATLAB codes. Results: : Gamma index analysis of film measurement in comparison with TPS calculated dose resulted in high pass rates >90% for tolerance criteria of 1%/1 mm. The isodose overlay and linear dose profiles of film measured and computed dose distribution on sagittal and coronal plane were in close agreement. Conclusions: : Through this study, the authors propose treatment verification QA method for Extend frame based fractionated Gamma Knife radiosurgery using EBT2 film.